Reconstruction of Aeolian Activity Variability in the Central Tibetan Plateau From Grain-Size Distributions: End-Member Modeling and Source Attribution of Sediments From Lake Selin Co - Zhang, Chunhui; Zhang, Wanyi; Liu, Yan; Yao, Jinjiao; Wan, Renchao; Li, Huwei; Hou, Xinyu; Zhang, Chengjun (Frontiers in Earth Science, 2022)
The grain size analysis and end-member modeling of clastic fractions in the Selin Co basin sedimentary sequence have revealed variations of aeolian activity in the central Tibetan Plateau since 3900 cal yr BP. The grain-size distributions measured in this study were classified into three statistical end members that may be connected to clastic material inputs from a variety of sources and transport processes. Among these, the EM3 fraction (modal grain size of ~138 μm) was suggested can indicate the aeolian activity history in the central Tibetan Plateau. The results indicate that the aeolian activity in this region occurred under dry and cold conditions since 3900 cal yr BP, with three strong aeolian activity intervals at 3200-2900 cal yr BP, 2400-1400 cal yr BP and after 130 cal yr BP. Comparison with other records showed that solar insolation, weakening Indian summer monsoon, and the strengthening Westerlies had/have a direct relationship with the aeolian activity in the central Tibetan Plateau. We therefore suggest that the atmospheric circulation patterns and effective humidity may have a strong impact on the water balance and weathering intensity in the arid and semi-arid areas, hence affecting dust emissions. And the coarse detrital end member fraction of lake sediments is suggested as a potential aeolian activity proxy.